Causal Associations Between Chronic Obstructive Pulmonary Disease and Common Comorbidities: Evidence from Comprehensive Genetic Methods - Ji J; Zhao Q; Yuan J; Yuan Z; Gao N (International Journal of COPD)
Jiadong Ji,1 Qian Zhao,1 Jie Yuan,2 Zhongshang Yuan,2 Nannan Gao3 1Institute for Financial Studies, Shandong University, Jinan, Shandong, People’s Republic of China; 2Department of Biostatistics, School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 3Department of Respiratory and Critical Care Medicine, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of ChinaCorrespondence: Nannan Gao, Department of Respiratory and Critical Care Medicine, Shandong Provincial Hospital Affiliated to Shandong First Medical University, No. 324, Jingwu Weiqi Road, Jinan, Shandong, 250021, People’s Republic of China, Tel +86 531 68773269, Email gaonan0570@163.comBackground: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease with high morbidity and mortality worldwide. Observational studies have shown correlations between common extrapulmonary comorbidities and COPD, but the existence of correlations does not necessarily prove a causal association. Therefore, causal relationships between diseases need to be explored by means of causal inference methods.Materials and Methods: Genetic correlation and two-sample Mendelian randomization (MR) analysis were explored to assess the causal relationship between exposures and outcomes with the genome-wide association studies (GWAS) dataset. Different sensitivity analyses were conducted to verify the robustness and consistency of results.Results: The linkage disequilibrium score regression showed that cardiovascular disease (CVD), hypertension (HTN) and type 2 diabetes mellitus (T2DM) were significantly genetically associated with COPD. T2DM and HTN were found to have a positive causal effect on COPD. The odds ratio (OR) of T2DM on COPD was 1.111 (95% CI, 1.063– 1.160; P< 0.0001) and that of HTN on COPD was 1.125 (95% CI, 1.084– 1.167; P < 0.0001). Similar results were verified by different MR methods. Furthermore, COPD had a positive causal effect on T2DM (OR 1.152 (95% CI, 1.064– 1.246; P=0.0005)).Conclusion: Our findings provided evidence for the causal association between HTN, T2DM and COPD, which would render new insights into the pathogenesis, prevention and intervention for COPD.Keywords: chronic obstructive pulmonary disease, cardiovascular diseases, type 2 diabetes mellitus, hypertension, Mendelian randomization, causal effect